Analisis Fungsi dan Makna Derivasi dan Infleksi dalam Novel “Ayah, Ini Arahnya Ke Mana, Ya?”: Analysis of the Function and Meaning of Derivation and Inflection in the Novel “Ayah, Ini Arahnya Ke Mana, Ya?” - Juni Agus Simaremare; Tetty Kristina Manurung; Bela Seftiani Simanjuntak; Ferlina Tamarisca Sinaga (Information Technology and Science(ITScience), 2026)
This study aims to describe and analyze the morphological forms and functions of derivation and inflection in the novel Ayah, Ini Arahnya ke Mana, Ya?. This study is motivated by the importance of understanding morphological processes in literary works, particularly how word formation contributes to meaning and language structure in narrative texts. This study uses a qualitative descriptive method. The research data source is the text of the novel Ayah, Ini Arahnya ke Mana, Ya?, and the data consist of words undergoing morphological processes of derivation and inflection. Data collection is carried out through listening and note-taking, and by carefully reading the text and noting the forms of words that undergo morphological processes. The collected data are analyzed using distributional methods to identify changes in word classes, affixation forms, and grammatical functions across language units. The results of the study show that the inflection process in the novel functions as a marker of grammatical relationships in sentences without changing the identity of the basic lexeme. The form of inflection is found in the use of affixes that mark certain grammatical aspects, so that the context of the sentence greatly influences their meaning.Meanwhile, the derivation process contributes to the formation of new words that may change word classes, such as verbs becoming nouns or adjectives. The meanings derived from the process reveal the formation of new semantic concepts that differ from their basic forms. Thus, these two morphological processes not only demonstrate the dynamics of word formation in Indonesian but also demonstrate linguistic functions that support the delivery of meaning in literary works.